Naphthyridine cyclopentadienyl chromium complexes as single-site catalysts for the formation of ultrahigh molecular weight polyethylene - Sieb, David; Wadepohl, Hubert; Enders, Markus (Organometallics, 2012)
Cyclopentadienyl ligands functionalized with a 1,5-naphthyridine donor have been used for the formation of chromium(III) half-sandwich complexes. In addition to standard analytical characterization, the complexes have been investigated by paramagnetic 1H NMR spectroscopy combined with DFT calculations. After activation, highly active single-site catalysts are obtained that lead to the formation of ultrahigh molecular weight polyethylene (UHMW-PE). Evaluation of polymer formation after different polymerization times at low temperature shows that the number of active centers is low at the beginning, but increases with polymerization time.